Structural analysis of an ergonomic motorcycle test rig using finite element analysis (FEA) / Muhammad Firdaus Azhar - Azhar, Muhammad Firdaus (2014)
As part of an effort to reduce global issue concerning motorcycle accidents, a motorcycle test rig named Postura Motergo was established. In validating the test rig’s design, structural analyses were performed for blue print approval prior to fabrication. Computer Aided Design (CAD) model of the test rig was analyzed using Generative Structural Analysis (GSA) package in the state-of-the-art CATIA V5R20 software. The motorcyclist’s weight and the material used as the test rig structure were the input into the Finite Element model. From there, the design was detailed out by the test rig’s design team before coming out with a final detail design which was also analyzed using FEA simulations. Tetrahedron mesh was used to generate the meshes on the finite element model. The boundary conditions were located at every area that was assumed to have zero degree of freedom (DOF) in real condition. The loading applied was 150kg taking a maximum average weight of a motorcyclist. Results showed that the test rig’s Von Mises Stress value was 1.79 x 108 MPa when 150kg of weight was applied. The yield strength of mild steel is 2.00 x 108 MPa and the factor of safety obtained was 1.12. With the positive results obtained from the FEA simulations, the Postura Motergo was approved for fabrication. In addition, the FEA proved that the design is safe to be used for motorcycle ergonomic researchers especially by the Motorcycle Engineering Test Lab (METAL). The public debut of the Postura Motergo was during the Invention, Innovation and Design Exposition 2014 (IIDEX 2014) managed to secure a Bronze medal under the Invention category. Furthermore, two academic research papers related to the Postura Motergo’s test rig were also accepted to be presented at two International Ergonomics Conferences; Applied Human Factor and Ergonomics 2014 and Ergonomics and Human Factors 2014.